Mesorectal shape variation in rectal cancer radiotherapy in prone position using a belly board. (July 2021) - Cox, Maurice C.; Braam, Pètra M.; Rütten, Heidi; van Leeuwen, Ruud; Wendling, Markus
Highlights: Mesorectal shape variation is diverse and largest in the upper-anterior region. Derived planning target volume margins for the upper-anterior region were larger in female patients. Planning target volume margins are comparable for radiotherapy and chemoradiotherapy groups. Abstract: Background and purpose: In rectal cancer patients, radiotherapy in prone position using a belly board can reduce the dose to organs at risk. For this patient group we investigated inter-fraction shape variation of the mesorectal part of the clinical target volume (CTV) and determined planning target volume (PTV) margins. Materials and methods: Patients with rectal cancer receiving neoadjuvant (chemo)radiotherapy were eligible. For each patient a planning computed tomography (pCT) and five cone-beam CT (CBCT) scans were acquired in prone position using a belly board. The mesorectal CTV was delineated on all scans. Mesorectal shape variation was quantified relative to the pCT. PTV margins were derived locally and averaged for separate subregions of the mesorectal CTV. For each patient a total PTV was constructed using our clinical margins for mesorectal and lymph node CTVs. An artificial dose distribution conforming to this PTV was used to calculate the coverage for the mesorectal CTV using the CBCT delineations. Results: In 19 rectal cancer patients the derived PTV margins were smallest in the upper-lateral region (6 mm) and largest in the upper-anterior region (16 mm). PTV margins for the upper-anterior region were larger for female patients (19 mm) compared to male patients (14 mm). Clinical margins for the total PTV were sufficient for a coverage of at least 97% of the mesorectal CTV for all patients. Conclusions: Mesorectal shape variation is heterogeneous and largest in the upper-anterior region, in rectal cancer patients irradiated in prone position and using a belly board.